2012
DOI: 10.2478/s11658-012-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead chloride on human erythrocyte membranes and on kinetic anion sulphate and glutathione concentrations

Abstract: Our study concerns the effects of exposure to lead chloride on the morphology, K + efflux, SO 4 -influx and GSH levels of the human erythrocyte. Blood was collected in heparinized tubes and washed three times. The cells were suspended at 3% hematocrit and incubated for 1 h at 25ºC in a medium containing increasing concentrations of lead chloride (0, 0.3, 0.5 and 1 µM). After incubation, the suspensions were centrifuged and the erythrocyte pellets were divided into three aliquots for testing. The results show: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…The increases in the levels of LPO in our Pd-exposed rats are thus directly indicating that Pd-poisoning induces a dropping down of the antioxidative defense and leads to hemolysis. Gugliotta et al (2012) [ 41 ] reported that the exposure of erythrocytes to Pb leads to a reduction in the average lifetime of the erythrocytes and the subsequent development of anemia. Though the mechanism(s) is not clearly known, one important effect of lead toxicity in erythrocytes consists of increasing intracellular calcium [Ca 2+ ](i), which in turn causes alterations in cell shape and volume and it is associated with cellular rigidity, hemolysis, senescence, and apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increases in the levels of LPO in our Pd-exposed rats are thus directly indicating that Pd-poisoning induces a dropping down of the antioxidative defense and leads to hemolysis. Gugliotta et al (2012) [ 41 ] reported that the exposure of erythrocytes to Pb leads to a reduction in the average lifetime of the erythrocytes and the subsequent development of anemia. Though the mechanism(s) is not clearly known, one important effect of lead toxicity in erythrocytes consists of increasing intracellular calcium [Ca 2+ ](i), which in turn causes alterations in cell shape and volume and it is associated with cellular rigidity, hemolysis, senescence, and apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…1, and the rate constants for SO 4 2- uptake are shown in Table 1. 5 µM DIDS was chosen to ensure total inhibition of the Band 3 protein [27,28]. NEM induces cell shrinkage and alterations in the redox state, as well as increases the phosphorylation of Band 3 at tyrosine residues [29].…”
Section: Resultsmentioning
confidence: 99%
“…Lead may also cause deficiency of the enzyme G-6PD (glucose-6 phosphate dehydrogenase) that may inhibit erythrocyte maturation in the bone marrow. (3,4) Gugliotta et al (24) investigated the effect of lead on the proteins in the erythrocyte membrane. Their results showed a decreased erythrocyte count, with membrane permeability playing an important role in the decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental laboratory study conducted by Gugliotta, (24) heparinized blood with hematocrit concentration of 3% was incubated for 1 hour at 25° C in a medium containing increasing concentrations of lead chloride (0, 0.3, 0.5 and 1 µM). The results of the study showed an increase in erythrocyte permeability with consequent cellular damage and death, particularly at high lead concentrations, changes in morphology and membrane structure of the red blood cell, and decreased erythrocyte ATP concentrations.…”
Section: Discussionmentioning
confidence: 99%